AKTYWNOŚĆ OBYWATELSKA MŁODZIEŻY WIEJSKIEJ - Krzyminiewska, Grażyna (Wydział Prawa i Administracji UAM, 2005)
The paper contains a report on civic activity of rural youth and identifies public spirits and attitudes currently prevailing among young people in Poland, basing on a research carried out on a group of 197 young respondents from rural areas in Poland.
CIVIC ACTIVITY OF RURAL YOUTH